Steroidomics of Pregnant Women at Advanced Age - Yu, Bin; Guo, Fang; Yang, Yuqi; Long, Wei; Zhou, Jun (Frontiers in Endocrinology, 2022)
Objectives To discover the profiles of different steroid hormones at the maternal-fetal interface and reveal the change characteristics in pregnant women at advanced maternal age (AMA). Methods Forty pregnant women were recruited in the study, including 20 AMA women (age ≥ 35) and 20 normal controls (age < 35 and without pregnancy complications). Among AMA women, 6 (AMA2) had pregnancy complications, and 14 (AMA1) had no complications. Their maternal blood (MB), placental tissue (P), and fetal cord blood (CB) were collected, and 18 different steroid hormone metabolites were analyzed by liquid chromatography tandem mass spectrometry (LC-MS/MS). Results The estradiol (E2) levels in MB were higher than those in P and CB. In contrast, the estrone (E1) and estriol (E3) levels were higher in P and CB. Compared with the progesterone levels (P4) in MB, those in P and CB were higher; however, cortisol (F) levels were deficient. In contrast, F in MB was maintained at an elevated level. Further, cortisone (E) levels in CB were higher than those in MB and P. Except for the decline of testosterone (T), androstenedione (A2) and Dihydrotestosterone (DHT), there were no significant differences in the other 15 steroid hormones in MB between the AMA1 and the control group (p>0.05). Compared with the AMA1 group, androgen levels were significantly higher in AMA2, especially in T (1.55 vs. 0.68 ng/ml, p=0.023), A2 (2.27 vs. 0.92 ng/ml, p=0.011) and Dehydroepiandrosterone (DHEA) (2.39 vs. 1.50 ng/ml, p=0.028). However, there were no significant changes in P and CB between two groups. Conclusion There are distribution rules and cascade changes of steroid profiles in maternal-fetal compartments. Significantly high androgen levels in AMA women have a positive relationship with adverse pregnancy complications.